PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR SYARI’AH LANTABUR TEBUIRENG JOMBANG - Muhammad Feri Nafi’; Lik Anah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the influence of leadership and work motivation on employee performance at PT BPR Syari’ah Lantabur Tebuireng Jombang. Employee performance is a crucial factor in determining organizational success, particularly in the banking sector, which demands high service quality, discipline, and professionalism. This research employed a quantitative approach using a census method, with all 39 employees serving as research respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The results indicate that leadership has a positive and significant effect on employee performance. Likewise, work motivation also shows a positive and significant influence on employee performance. Simultaneously, leadership and work motivation significantly affect employee performance. These findings confirm that effective leadership practices and strong work motivation contribute substantially to improving employee performance. The study implies that management should strengthen leadership quality and consistently foster employee motivation to enhance organizational performance sustainably.